GREEN MANAGEMENT SEBAGAI PELAKSANAAN ETIKA BISNIS UPAYA KELANGSUNGAN HIDUP PERUSAHAAN JANGKA PANJANG - Triastity, Rahayu - (Universitas Slamet Riyadi, 2011)
ABSTRACT New challenges in global competition is how companies can survive and thrive based on economic logic that links the environment, production resources, innovation and competitive advantage. This article discusses the activities of the company based on ethics, especially those related to environmental ethics through Green Management approach. The importance and necessity of the world Indonesia business role in Saving the environment is time to begin. It's no longer just rhetoric, but it should be an integral part of corporate strategy and the part of management thinking. Through the Green Management, can the industry play a role as well as carry out activities of its business ethics? Is a thing to the contrary between the achievement of strategic corporate objectives with the implementation of ethical business through green management? Is the Green Management can make the company sustainable life? Through a green approach to ethics management in business activity the company is expected to be able to live sustainably on the one hand and on the other hand is able to contribute to. Stakeholders, and more broadly is to play a part in saving the environment and the universe. If companies start doing, is expected to mobilize and involve stakeholders to also do this. No matter how small something is done but done consistently and continuously, the result undoubtedly be very meaningful to the lives of the environment and its contents. Keywords: Business ethics, green management, sustainability, competitive strategy.